2005
DOI: 10.21273/jashs.130.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration Capacity in Poinsettia Cuttings at Different Rooting Stages and the Development of a Cutting Coefficient for Scheduling Mist

Abstract: Rooting stage, transpiration capacity, and relative water content were measured in cuttings every 5 days for 25 days. Cell divisions in phloem parenchyma were evident between 5 and 10 days after sticking, organized subcuticular root primordia were present between 10 and 12 days, and roots emerged between 12 and 15 days. Transpiration was measured in poinsettia (Euphorbia pulcherrima Willd. ex Klotzsch `Freedom Dark Red') cuttings under light or dark conditions at increasing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…may be slow to form adventitious roots and the cuttings disintegrate prior to the formation of functional roots (Rose and Pellett 1994;Stankova and Panetsos 1997;Voyiatzi et al 2002). Species where roots emerge rapidly are often categorized as 'easy to root' (Wilkerson et al 2005) in contrast to those more 'difficult to root' ones that require longer periods before emergence of roots (Tarrago et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…may be slow to form adventitious roots and the cuttings disintegrate prior to the formation of functional roots (Rose and Pellett 1994;Stankova and Panetsos 1997;Voyiatzi et al 2002). Species where roots emerge rapidly are often categorized as 'easy to root' (Wilkerson et al 2005) in contrast to those more 'difficult to root' ones that require longer periods before emergence of roots (Tarrago et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A decline in tissue nutrient concentration was also observed in poinsettia (Euphorbia pulcherrima Willd. ex Klotsch) after 7 d under mist, and this decline was not correlated with three different rates of water volume applied (Wilkerson and Gates, 2005). A decline in tissue nutrient concentration also occurred in poinsettias that did not have any water applied to foliage 13 d after sticking (Svenson and Davies, 1995).…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, commercial fertilizer application early in propagation before root formation may be required to recharge leached nutrients from the substrate. Water-soluble fertilizer applications before root emergence may also facilitate foliar uptake of nutrients (Tukey et al, 1958) and reduce observed tissue nutrient declines during preliminary phases of propagation (Svenson and Davies, 1995;Wilkerson and Gates, 2005).…”
mentioning
confidence: 99%
“…Zinc and Mg were also lost from the upper stems (Table 1). Nutrient leaching typically occurs in cuttings under intermittent mist (Tukey, 1978;Wilkerson et al, 2005;Wott and Tukey, 1967). Although decreases in tissue nutrient concentration can also be due to dilution, this would require growth and expansion of the cutting (Blazich, 1988;Blazich et al, 1983;Svenson and Davies, 1995).…”
Section: Resultsmentioning
confidence: 99%